Strategy Protection Consumer in E-commerce Transactions : An Overview Law and Implementation - Hulman Panjaitan; Andrew Betlehn (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Study This to study strategy protection consumer in e-commerce transactions with based on analysis law and its application. Through studies library, information collected from sources in the form of journals, articles, and relevant regulations, to to obtain broad understanding about method law protect consumers in the realm of e-commerce and the realization practical from law The results of the study show that although there is various initiative legislative For protect consumers, still There is a number of challenge in its implementation, which includes difference regulation between countries, difficulties in enforcement law, and lack in protection consumers by applicable law. Research this also found importance increase awareness and education consumer about rights they For optimize level protection that can obtained. Research This recommend improvement Work The same international in standardization regulation, strengthening monitoring and enforcement law, and improvement education consumer as step crucial For repair protection consumer in e-commerce. It is hoped that recommendations This Can made into reference by manufacturer policies, e-commerce players, and consumers For increase standard protection in the digital era.